Differences in the Flexibility of Switching Learning Strategies and CREB Phosphorylation Levels in Prefrontal Cortex, Dorsal Striatum and Hippocampus in Two Inbred Strains of Mice - Cho, Woo-Hyun; Han, Jung-Soo (Frontiers in Behavioral Neuroscience, 2016)
Flexibility in using different learning strategies was assessed in two different inbred strains of mice, the C57BL/6 and DBA/2 strains. Mice were trained sequentially in two different Morris water maze protocols that tested their ability to switch their learning strategy to complete a new task after first being trained in a different task. Training consisted either of visible platform trials (cued training) followed by subsequent hidden platform trials (place training) or the reverse sequence (place training followed by cued training). Both strains of mice showed equivalent performance in the type of training (cued or place) that they received first. However, C57BL/6 mice showed significantly better performances than DBA/2 mice following the switch in training protocols, irrespective of the order of training. After completion of the switched training session, levels of cAMP response element-binding protein (CREB) and phosphorylated CREB (pCREB) were measured in the hippocampus, striatum, and prefrontal cortex of the mice. Prefrontal cortical and hippocampal pCREB levels differed by strain, with higher levels found in C57BL/6 mice than in DBA/2 mice. No strain differences were observed in the medial or lateral region of the dorsal striatum. These findings indicate that the engagement (i.e., CREB signaling) of relevant neural structures may vary by the specific demands of the learning strategy, and this is closely tied to differences in the flexibility of C57BL/6 and DBA/2 mice to switch their learning strategies when given a new task.